Six propositions for care-centric planning and governance that promote sustainable cities - Romina Rodela; Miriam Williams; Johanna Ohlsson; Ida Sandström (npj Urban Sustainability)
Abstract This Perspective suggests six conceptual propositions to advance care-centric planning and governance in support of SDG 11. By prioritizing relationships, responsiveness, and collective well-being, while also integrating empowerment, environmental stewardship, and cultural diversity, a care-centric approach fosters more inclusive and sustainable cities. Drawing on selected practice-based examples, we illustrate care’s potential to inspire novel governance approaches, and to stimulate discussion about urban planning for more just and resilient urban environments.